Pembangunan Intelektualitas dan Kualitas Diri Perempuan sebagai Kekuatan untuk Menjadi Pemimpin dalam Era Globalisasi - Manurung, Rosida Tiurma (Zenit, 2012)
Can Indonesian women become a leader? To be a leader, one needs to be responsible, decisive,  ready to take risks,  consistent,  physically  fit, and able to manage his/her subordinates. Generally speaking, such qualities are rarely found in women. In fact, women are more dominated by their emotion, anxieties, unwillingness to take risks, and less knowledgable than men.  To became a leader, a woman must equip herself with optimal intellect and self improvement. If a woman can show brilliant intelligence and pleasing personality, she can become a leader. The author is interested  in  researching on the improvement  of  Indonesian women’s intellectual and personal qualities in the hope that these research tips, steps, or effort to enhance a wo,an’s dignity can be beneficial to women in Indonesia.   Keywords: intellectual improvement, self improvement , the power of women as leaders